A Study Of Teacher-Student Relationships In The Works Of Hussain Voiz Kashifi “Akhloqi Mohsini” and “Futuvvatnamai Sultani” - Rakhmatov Nuriddin Negkadamovich (Penerbit Jurnal Indonesia, 2024)
Husayn Voiz Kashifi simply and fluently describes the personal, moral, legal, and social qualities of young people, explains the different aspects of this order from other orders, and also describes in detail the qualities that foster these requirements and qualities in young people. The path of this order is difficult and complex. Therefore, the pir acts as a guide so that young people who choose this path do not go astray and are not distracted by various people.